Use Cases and Impact of Audio-Based Virtual Exploration - Ross, Anne Spencer; Cutrell, Ed; Fiannaca, Alex; Kneisel, Melanie; Morris, Meredith Ringel (CHI 2019 Workshop on Hacking Blind Navigation, 2019)
Audio-based virtual navigation experiences present an opportunity for people who are blind or have low vision to increase their familiarity with an area before traveling. Such experiences could also increase people’s excitement and confidence in exploring places. As a preliminary investigation, we developed the Audio-based Virtual Exploration (AVE) app. In a user study with 14 people who were blind or had low vision, we explored use cases of virtual navigation, how app features could support those uses, and how the experience could impact mental maps and interest and comfort in travel. Participants proposed using virtual experiences for navigation, exploration, and augmented reality. We present research questions around developing experiences to support these use cases and defining metrics of success.